Development, Optimization, and Validation of a Quantitative PCR Assay for Borrelia burgdorferi Detection in Tick, Wildlife, and Human Samples - Julie Lewis; Vett K. Lloyd; Gilles A. Robichaud (Pathogens)
Tick-borne pathogens are growing in importance for human and veterinary research worldwide. We developed, optimized, and validated a reliable quantitative PCR (qPCR; real-time PCR) assay to assess Borrelia burgdorferi infection by targeting two B. burgdorferi genes, ospA and flaB. When assessing previously tested tick samples, its performance surpassed the nested PCR in efficiency, sensitivity, and specificity. Since the detection of Borrelia is more difficult in mammalian samples, the qPCR assay was also assessed using wildlife tissues. For wildlife samples, the sensitivity and specificity of ospA primers, with the incorporation of a pre-amplification step, was equivalent or superior to the nested PCR. For human samples, no primer set was successful with human tissue without culture, but we detected Borrelia with ospA and flaB primers in 50% of the Lyme culture samples, corresponding to 60% of the participants with a Lyme disease diagnosis or suspicion. The specificity of amplification was confirmed by Sanger sequencing. The healthy participant culture samples were negative. This PCR-based direct detection assay performs well for the detection of Borrelia in different biological samples. Advancements in detection methods lead to a better surveillance of Borrelia in vectors and hosts, and, ultimately, enhance human and animal health.